Peran Pendidikan Kewarganegaraan Dalam Membentuk Etika Sosial Remaja Di Era Modern - Meserius Harefa (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
Rapid social changes driven by globalization and technological advancements have significantly influenced how adolescents think, behave, and interact in their daily lives. Amid these challenges, Civic Education (PKn) plays a strategic role in shaping adolescents' social ethics to uphold moral and humanitarian values. This study aims to examine the role of Civic Education in developing adolescents’ social ethics in the modern era, as well as to explore relevant challenges and learning strategies. The research method used is a literature review by analyzing various scholarly journals, academic books, and relevant research reports. The findings indicate that Civic Education can serve as an effective medium for instilling social values such as empathy, responsibility, tolerance, and justice, particularly through interactive and contextual learning approaches. However, its effectiveness is greatly influenced by external challenges such as the impact of social media, individualistic cultural trends, and a lack of role models in the surrounding environment. Therefore, innovative teaching methods, integration of digital technology, and collaboration between schools, families, and communities are needed to strengthen the role of Civic Education as a foundation for character education among adolescents.